1971
DOI: 10.1111/j.1365-2362.1971.tb00642.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Lecithin: Cholesterol Acyltransferase Activity in Liver Disease*

Abstract: Abstract. In liver disease the proportion of plasma cholesterol present in the form of ester is lower than that found in normal subjects. Recent work has suggested that a plasma enzyme, lecithin: cholesterol acyltransferase (LCAT), may be a major f actorin the physiological regulation of plasma cholesterol ester levels. In patients with a variety of hepatobiliary disorders LCAT activity was found to be reduced and a study of the effects of interaction between normal and jaundiced plasmas supported the hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1973
1973
1999
1999

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…The observed decrease in serum phospholipids is supported by two other reports in patients with certain types of malignant tumours (Nydegger & Butler, 1972) and those with advanced liver disease and malignancy (Calandra et al, 1971). Again this observation supports the theory that the presence of cancer affects the metabolic controls within the liver.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The observed decrease in serum phospholipids is supported by two other reports in patients with certain types of malignant tumours (Nydegger & Butler, 1972) and those with advanced liver disease and malignancy (Calandra et al, 1971). Again this observation supports the theory that the presence of cancer affects the metabolic controls within the liver.…”
Section: Resultssupporting
confidence: 83%
“…This enzyme is produced in the liver and it has been reported that in liver disease, (Calandra et al, 1971). The lack of alteration in liver enzymes in this study implied that the function of the liver was unimpaired.…”
Section: Resultsmentioning
confidence: 49%
“…IOc). Because in acute hepatitis the synthetic capacity of the liver is not impaired, the low level of Apo A is probably due to an increased catabolism of the apolipoprotein after reduction of LCAT activity described by several authors (Simon and Scheig, 1970;Calandra et al, 1971;Gjone et al, 1971) in acute hepatitis.…”
Section: Resultsmentioning
confidence: 96%
“…Its results are thought to represent activity of the enzyme in vivo (Norum, 1974). There is evidence to suggest that low LCAT activity found in patients with liver disease is usually due to a reduction in enzyme concentration rather than to abnormality of the substrate (Calandra et al, 1971;Simon, 1974). In normal subjects and in patients with obstructive and parenchymal liver disease there is a good correlation between the results of the Stokke & Norum (1971) method and those obtained with the method of Glomset & Wright (1964) (Blomhoff, Skrede & Ritland, 1974); the results of the latter method are thought to depend largely on enzyme concentration (Glomset & Wright, 1964).…”
Section: Methodsmentioning
confidence: 96%